2022
DOI: 10.3389/fmed.2022.871528
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Placenta Increta With High-Intensity Focused Ultrasound Ablation and Leaving the Placenta in situ: A Multicenter Comparative Study

Abstract: ObjectiveTo explore the feasibility of simple high-intensity focused ultrasound (HIFU) ablation for placenta increta.MethodsNinety-five patients after a vaginal delivery were enrolled in this retrospective cohort study, 53 patients were treated with simple HIFU ablation, and 42 patients were treated with HIFU followed by uterine curettage.ResultsAll 95 patients were successfully treated with a single-session HIFU procedure, and in the control group, the necrotic placental tissue was removed with curettage. Vag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…High frequency focussed ultrasound for placenta increta has shown promising results in observational studies, including those in which the placenta is left in situ [ 93 ].…”
Section: High Frequency Focussed Ultrasound For Placenta Incretamentioning
confidence: 99%
“…High frequency focussed ultrasound for placenta increta has shown promising results in observational studies, including those in which the placenta is left in situ [ 93 ].…”
Section: High Frequency Focussed Ultrasound For Placenta Incretamentioning
confidence: 99%
“…HIFU can be used to deliver high-energy dense ultrasound waves at a focal point within a patient's uterus to expedite coagulative necrosis following delivery and repair the uteroplacental defect via thermal ablation. 40 Although preliminary studies have shown the safety and efficacy of HIFU in treating PAS, further investigations should be performed to assess whether HIFU impacts ovarian reserve and pregnancy outcomes in young women. 41,42…”
Section: Future Trendsmentioning
confidence: 99%